2000
DOI: 10.1590/s1517-83822000000100006
|View full text |Cite
|
Sign up to set email alerts
|

Homology among extra-cryptic DNA bands and the typical plasmids in Brazilian Yersinia pestis strains

Abstract: Yersinia pestis, the etiologic agent of plague, harbors three well-characterized plasmids: pFra (90-110kb), pYV (70 kb) and pPst (9.5 kb). Furthermore, some extra-cryptic DNA bands have been observed in a number of wild strains from several foci of the world. Additional bands have also been reported in Brazilian strains. Looking for any relationship among these cryptic DNA bands and the three-prototypical plasmids, we analyzed twelve strains displaying different plasmid content. The DNA bands were hybridized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…Leal-Balbino et al (2004 and Leal et al (2000) observed spontaneous alterations in the genome (plasmid and chromosomal) of Brazilian Y. pestis as a result of prolonged storage and handling in the laboratory. The stability of the PFGE profiles was investigated by the analysis of serial subcultures of three strains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Leal-Balbino et al (2004 and Leal et al (2000) observed spontaneous alterations in the genome (plasmid and chromosomal) of Brazilian Y. pestis as a result of prolonged storage and handling in the laboratory. The stability of the PFGE profiles was investigated by the analysis of serial subcultures of three strains.…”
Section: Discussionmentioning
confidence: 99%
“…Pigmentation segment deletion and plasmid deletions in Brazilian strains have been reported (Almeida et al, 1994;Leal et al, 2000;Leal-Balbino et al, 2006). Moreover, Guiyoule et al (1994) found a pigmentation deletion in vitro, which gave a new PFGE type, although they did not suggest that all new PFGE types were due to this deletion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the strains could be inaccurate representatives of the original isolates, and these differences could be due to handling procedures during the prolonged storage of the strains in the laboratory since their isolation (Revazishvili et al, 2008;Vogler et al, 2011). Leal et al (2000) and Leal-Balbino et al (2004, 2006 observed spontaneous changes in the genome (both plasmid and chromosomal) of Brazilian Y. pestis following prolonged storage and laboratory handling. However, analysis of the 12 VNTR loci in the three parental strains and their derived cultures did not reveal changes in the studied regions, confirming their stability as previously observed (Adair et al, 2000;Keim et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…pestis strains lacking plasmids or carrying additional cryptic plasmids have also been found in nature (Filippov et al 1990;Balakhonov et al 1991). In a later study, Leal et al (2000) showed that a 30 kb atypical DNA band is probably a larger form of pPst and that a >90 kb DNA band could comprise open circular or linearized form of the pFra and pYV plasmids. In a later study, Leal et al (2000) showed that a 30 kb atypical DNA band is probably a larger form of pPst and that a >90 kb DNA band could comprise open circular or linearized form of the pFra and pYV plasmids.…”
Section: Introductionmentioning
confidence: 95%